Storytelling a disaster awareness tool among kindergarten pupils - Tolentino, Marie Antonette; Vergara, Helga P.; Albor, Rufo Gil Z. (2017)
This study aimed to expiore the effectiveness of storytelling as a disaster awareness tool in improving children's understanding of typhoons. The study probed into children's understanding of a typhoons. The study probed into children's understanding of a typhoon in terms of knowledge of typhoon definition and effects; recognition of activities before, during and after a typhoon; definition of typhoon occurrence; and identification of ways to give aid to typhoon victims. The Narrative Story Stem Techniques was used to elicit responses to a sample of 37 kindergarten respondents from a private school in Laguna. A pre-test and post-test approach was administered to look into changes with children's knowledge on typhoons after the storytelling activity. Results of the comparison between the pre-test and post-test responses showed that children have a little to no knowledge of typhoons before the storytelling activity. Likewise, results from the paired t-test revealed that the children's scores significantly increased after the storytelling activity. These findings provide preliminary evidence that storytelling can be an effective tool in teaching children about disaster awareness, particularly on typhoons.
Keywords: Disaster Awareness Tool - Storytelling